The Perspective of the Islamic Community on the Existence of the Mbah Gandrung Puppet in Kediri Regency - Umi Colbyatul Khasanah,; Pamungkas, Jati (Journal of Islamic and Social Studies, 2025)
This research uses qualitative methods with a phenomenological approach to make it easier for researchers to explore the meaning of concepts and personal experiences based on awareness, this awareness occurs in the self differently from each individual. By using Blumer's theory of analysis, namely Symbolic Intersectionalism to explain the position of the puppeteer (human being) who gives a hidden message or meaning of cultural values through puppetry Mbah Gandrung which he played to the audience (community). The result of this research is that the Islamic community in Pagung Village has the assumption that the Mbah Gandrung puppet has its own mystical side. Wayang Mbah Gandrung is also a punden in Pagung Village. Making the wayang Mbah Gandrung respected its existence by the community. The community is also grateful for the existence of the Mbah Gandrung puppet because it is a cultural heritage owned by Pagung Village. The existing changes in the performance of the Mbah Gandrung puppet coupled with Islamic prayers make people not think that responding to the Mbah Gandrung puppet is to confirm God. There has never been a conflict between Mbah Gandrung puppets because the community understands that this Mbah Gandrung puppet is also included in the artistic heritage that is owned by the dam must be preserved.